Impact of Mandatory Measles Vaccination on Coverage in Italy and the European Union: an observational study - Gaeta, Maddalena; Fugazza, Simone; Carbone, Matteo; Marjin, Corina; Parrini, Andrea; Raso, Eleonora; Viviani, Luca; Odone, Anna (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Measles is a highly contagious disease, but it is preventable through vaccination. Despite the availability of measles vaccines, outbreaks continue to occur, due to factors such as vaccine hesitancy. In Italy, measles vaccination has been mandatory since 2017. Methods. This study analyses vaccination coverage trends to assess the impact of this mandatory vaccination policy at regionjqal, national, and European Union levels. Results. Results show a significant increase in measles vaccination coverage within Italy following implementation of the mandate, both at the national (+5,2%) and regional levels. However, the comparison of European countries with and without mandatory vaccination policies did not reveal statistically significant differences in coverage. Conclusion. This suggests that while mandatory vaccination can improve coverage within a nation, additional strategies may be needed to address vaccine hesitancy and achieve herd immunity across broader geographical areas.